A Comprehensive Review on Microstrip Couplers: Structure, Design Method and Performance - Rezaei, Abbas; Yahya, Salah I.; Nouri, Leila (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
In this work, several types of microstrip couplers are investigated in terms of structure, performance and design methods. These planar 4-ports passive devices transmit a signal through two different channels. Designers' competition has always been in miniaturizing and improving performance of couplers. Some couplers have been offered with a novel structure, which is a special feature. A high-performance coupler should have high isolation and low losses at both channels. The channels are usually overlapped so that the common port return loss in these channels should be low. Among the couplers, those with balanced amplitude and phase are more popular. The popular mathematical analysis methods are even/odd mode analysis, extracting the information from the ABCD matrix and analyzing the equivalent LC circuit of a simple resonator. According to the phase shift value, couplers are classified as 90º and correct multiples of 90º, where a microstrip 0º coupler can be used as a power divider. Some couplers have filtering and harmonic elimination features that are superior to other couplers. However, few designers paid attention to suppressing the harmonics. If the operating frequency is set in according to the type of application, the coupler becomes particularly valuable.ABCD Matrix